Bellies, bowels and entrails in the eighteenth century. ([Place of publication not identified] : MANCHESTER UNIV Press, 2018)
This collection of essays seeks to challenge the notion of the supremacy of the brain as the key organ of the Enlightenment, by focusing on the workings of the bowels and viscera that so obsessed writers and thinkers during the long eighteenth-century. These inner organs and the digestive process acted as counterpoints to politeness and other modes of refined sociability, drawing attention to the deeper workings of the self. Moving beyond recent studies of luxury and conspicuous consumption, where dysfunctional bowels have been represented as a symptom of excess, this book seeks to explore other manifestations of the visceral and to explain how the bowels played a crucial part in eighteenth-century emotions and perceptions of the self. The collection offers an interdisciplinary and cross-cultural perspective on entrails and digestion by addressing urban history, visual studies, literature, medical history, religious history, and material culture in England, France, and Germany.
Iconography of the belly: eighteenth-century satirical printsVisceral visions: art, pedagogy and politics in Revolutionary France; The saints of the entrails and the bowels of the earth; Select bibliography; Index
Print version record.
Includes bibliographical references and index.
In English.
JSTOR
Keywords: Enlightenment; Human body (Philosophy); Self; Ego; Siècle des Lumières.; Corps humain (Philosophie); Moi (Psychologie); Enlightenment (18th-century western movement); HISTORY -- Europe -- Western; HISTORY -- Europe -- France; Enlightenment; Human body (Philosophy); Self